QUALITY ASSESSMENT OF SINGLE-PASS CORNER STEEL WELDED JOINTS - Praunseis, Zdravko; Stergar, Bojan; Brinovar, Iztok (Journal of Energy Technology, 2023)
The aim of this paper is to analyse the quality assessment of single-pass corner steel welded joints. The testing revealed the most burdened welded joints, which were cut out of the workpiece and prepared for metallographic macroscopic and microscopic analysis. Thus, for all examinations of single-pass corner steel welded joints, the standard test procedures were used to determine the weldability and quality assessment of base materials and welded joints. Additionally, the effects of various welded defects of single-pass weld material on the bearing strength of corner welded joints will be analysed.